In vitro and in vivo anti-tumour effects of coconut water vinegar on 4T1 breast cancer cells - Mohamad, Nurul Elyani; Yeap, Swee Keong; Abu, Nadiah; Kian, Lam Lim; Zamberi, Nur Rizi; Nordin, Noraini; Sharifuddin, Shaiful Adzni; Long, Kamariah; Mohammed Alitheen, Norjahan Banu (Swedish Nutrition Foundation, 2019)
Background: Coconut water and vinegars have been reported to possess potential anti-tumour and immunostimulatory effects. However, the anti-tumour, anti-inflammatory and immunostimulatory effects of coconut water vinegar have yet to be tested. Objective: This study investigated the in vitro and in vivo anti-tumour effects of coconut water vinegar on 4T1 breast cancer cells. Methods: The 4T1 cells were treated with freeze-dried coconut water vinegar and subjected to MTT cell viability, BrdU, annexin V/PI apoptosis, cell cycle and wound healing assays for the in vitro analysis. For the in vivo chemopreventive evaluation, mice challenged with 4T1 cells were treated with 0.08or 2.00 mL/kg body weight of fresh coconut water vinegar for 28 days. Tumour weight, apoptosis of tumour cells, metastasis and immunity of untreated mice and coconut water vinegar-treated 4T1 challenged mice were compared. Results Freeze-dried coconut water vinegar reduced the cell viability, induced apoptosis and delayed the wound healing effect of 4T1 cells in vitro. In vivo, coconut water vinegar delayed 4T1 breast cancer progression in mice by inducing apoptosis and delaying the metastasis. Furthermore, coconut water vinegar also promoted immune cell cytotoxicity and production of anticancer cytokines. The results indicate that coconut water vinegar delays breast cancer progression by inducing apoptosis in breast cancer cells, suppressing metastasis and activating anti-tumour immunity. Conclusion: Coconut water vinegar is a potential health food ingredient with a chemopreventive effect.